1999
DOI: 10.1007/s002130050844
|View full text |Cite
|
Sign up to set email alerts
|

Can the ”state-dependency" hypothesis explain prevention of amphetamine sensitization in rats by NMDA receptor antagonists?

Abstract: Many laboratories have reported that coadministration of N-methyl-D-aspartate (NMDA) receptor antagonists with psychomotor stimulants prevents the development of behavioral sensitization and therefore concluded that NMDA receptor transmission is necessary for sensitization. According to an alternative "state-dependency" interpretation, NMDA receptor antagonists do not prevent sensitization. Rather, they become a conditioned stimulus for the sensitized response, i.e., it is only elicited in response to combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
3
26
1
Order By: Relevance
“…Selective ablation of NR1 expression in striatal neurons has been used to study the role of NMDA receptor signaling in the acquisition of behavioral sensitization and conditioned place preference (Heusner and Palmiter, 2005;Agatsuma et al, 2010). These studies clarify previous research showing that blockade of NMDA receptor is disruptive to the development of sensitization and place preference (Haracz et al, 1995;Kim et al, 1996;Li and Wolf, 1999).…”
Section: Introductionsupporting
confidence: 55%
“…Selective ablation of NR1 expression in striatal neurons has been used to study the role of NMDA receptor signaling in the acquisition of behavioral sensitization and conditioned place preference (Heusner and Palmiter, 2005;Agatsuma et al, 2010). These studies clarify previous research showing that blockade of NMDA receptor is disruptive to the development of sensitization and place preference (Haracz et al, 1995;Kim et al, 1996;Li and Wolf, 1999).…”
Section: Introductionsupporting
confidence: 55%
“…Despite these differences, however, the behavioral findings with amphetamine are consistent with those of cocaine. Competitive, non-competitive, and glycine-site NMDAR antagonists interfere with both the acute and sensitized responses to amphetamine [45,46,27,47,48,52].…”
Section: Discussionmentioning
confidence: 99%
“…For example, her lab [52] found that CGS19755 produced a "clean block" of sensitization by preventing any increase in amphetamine-induced activity across training days and during the sensitization challenge test. However, in both this and a prior study [27], the acute response to amphetamine was dramatically increased when CGS19755 was coadministered (compare [52], their Figs. 1A and 2A, day 1 response for amphetamine only and amphetamine with CGS19755 and [27], their Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations